2023
DOI: 10.1101/2023.04.27.538576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

p53 promotes revival stem cells in the regenerating intestine after severe radiation injury

Abstract: Ionizing radiation induces cell death in the gastrointestinal (GI) epithelium by activating p53. However, p53 also prevents animal lethality caused by radiation-induced GI injury. Through single-cell RNA-sequencing of the irradiated mouse intestine, we find that p53 target genes are specifically enriched in stem cells of the regenerating epithelium, including revival stem cells that promote animal survival after GI damage. Accordingly, in mice with p53 deleted specifically in the GI epithelium, ionizing radiat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Furthermore, these reprogramming clusters are accompanied by distinct patterns of gene expression. Reprogramming secretory cells upregulate TP53 and the YAP1 target gene CLU, while SC- associated cells exhibit an upregulation of YAP1, TP53, and IL33 consistent with previous observations in mouse models following radiation injury 50,51 . In contrast, reprogramming colonocytes display an upregulation of AREG, PLAUR, and CXADR 52,53 (Figure 5B).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, these reprogramming clusters are accompanied by distinct patterns of gene expression. Reprogramming secretory cells upregulate TP53 and the YAP1 target gene CLU, while SC- associated cells exhibit an upregulation of YAP1, TP53, and IL33 consistent with previous observations in mouse models following radiation injury 50,51 . In contrast, reprogramming colonocytes display an upregulation of AREG, PLAUR, and CXADR 52,53 (Figure 5B).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, we hypothesize that these cells are likely to conclude the regenerative process. The transition to a fetal-like state following damage has been reported in mice 4,6,50,75 and recently in a human in vitro and in vivo study as a crucial step in metastatic growth during colorectal cancer (CRC) progression 76,77 . Indeed, comparison of our in vitro study to an in vivo dataset of metastatic CRC progression revealed similarities between the SC Start state and stem cells of primary and metastatic tumor tissue (data not shown) 76 .…”
Section: Discussionmentioning
confidence: 98%
“…The uniquely expressed AF proteins were associated with mitochondrial translation elongation, mitochondrial translation termination, transcriptional regulation via TP53, cellular response to stress, and regulation of TP53 activity (Supplementary Figure S3). A recent study showed that TP53 plays a crucial role in stimulating the recovery of stem cells within the regenerating intestine following extensive radiation damage . While exposed to hormonal or chemical triggers, TP53 actively stimulates the differentiation of both mouse and human embryonic stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that TP53 plays a crucial role in stimulating the recovery of stem cells within the regenerating intestine following extensive radiation damage. 23 While exposed to hormonal or chemical triggers, TP53 actively stimulates the differentiation of both mouse and human embryonic stem cells. 24 In the present work, alcohol may act as a trigger for TP53-mediated functions.…”
Section: Discussionmentioning
confidence: 99%
“…Undeniably, all findings in this study based on the comparison with and without CUL4B deletion in the intestinal epithelium, revealing CUL4B as a novel regulator of p53 in IR-induced apoptosis. In addition, a contrasting perspective has emerged in the function of p53, which prevents genotoxicity caused by IR through inducing revival and decreasing apoptosis of stem cells to reinstate intestine integrity 31 , 32 . Whether the protective property of p53 is related to CUL4B and various effects of downstream molecules of p53 seem to be further detected.…”
Section: Discussionmentioning
confidence: 99%